(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, there is a general understanding of physical load and facts about the pedagogical features of physical exercise load. Also, the effect of physical loads on the body of the athletes, the use of such concepts as fatigue and exhaustion in today’s training sessions are covered in detail.